(untitled) (Bangladesh Journal of Zoology, 2015)
A total of 6 species of freshwater mussels under the family Unionidae, order- Unionoida were collected, which are new records for Bangladesh. The information on the distribution and ecology, population density and seasonal variation of Lamellidens phenchooganjensis, L. indawgyiensis, L. generosus, Parreysia (Parreysia) favidens var. assamensis, P. (P.) var. marcens and P. (P.) var. viridula were provided in this paper. Population density and morphometric parameters were measured. Moreover, economic importance and economic role were stated. Bangladesh J. Zool. 41(1): 29-42, 2013